The Effectiveness of CIRC (Cooperative Integrated Reading and Composition)-Based Learning Model on Elementary School Students' Writing Ability in Subjects Indonesian a Systematic Literature Review - Satriani Prilestari; Karsoni Berta Dinata (Universitas Pendidikan Ganesha, 2025)
This study aims to examine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model on the writing ability of elementary school students through the Systematic Literature Review (SLR) approach. Data were obtained from eight scientific articles published between 2020 and 2025 and analyzed systematically using five main stages in SLR, namely identification, screening, feasibility, inclusion, and data synthesis. The results showed that the CIRC model consistently improved students' writing skills on various types of texts, including exposition texts, free essays, summaries, and introductory writing. In addition, this model also increases the activeness, cooperation, and involvement of students in the learning process. The CIRC model has proven to be superior to other methods such as Mind Mapping in the context of improving writing skills. With a collaborative and fun learning approach, CIRC can be an alternative effective learning strategy in Indonesian learning in elementary schools. This research makes an important contribution to the development of cooperative-based learning practices to improve students' writing skills more optimally.